Gender Diversity as the Moderating Effect on Tax Avoidance, Economic Value Added, and Firm Value: A Study of Companies Listed on Indonesia Stock Exchange 2015-2019 - Sesilia Rukti Pertiwi; Wiwiek Prihandini (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Gender diversity gives equal opportunities for women and men to occupy key positions in the company’s management. This study aims to reveal the role of women sitting on the executive boards in strengthening the effect of tax avoidance and economic value added (EVA) on firm value. Model testing was carried out on 59 manufacturing companies in the consumer goods industry listed on the Indonesia Stock Exchange in 2015-2019. The data were analysed using the multiple linear regression processed by Eviews. The results of this study indicate that tax avoidance has no effect on firm value, while EVA has a positive effect on firm value. Furthermore, gender diversity weakens the effect of EVA on firm value, but gender diversity is not proven to moderate the effect of tax avoidance on firm value. Keywords: tax avoidance, EVA, firm value, gender diversity